Late proximal pulmonary artery occlusion in a child with a single chamber after a right-sided Blalock-Taussig shunt - Nałęcz, Tomasz; Mroziński, Bartłomiej; Moszura, Tomasz; Wojtalik, Michał (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The paper presents the management of a child born with pulmonary valve atresia, a single (double-inlet) ventricle, right ventricular hypoplasia, and perimembranous septal defect. The first stage of treatment consisted in a Blalock-Taussig shunt. Control angiography performed 1 year after surgery confirmed that the anastomosis was correct, and there was no narrowing at the connection. The first stage of treatment was complicated by the occlusion of the left pulmonary artery, as diagnosed during cardiac catheterization before the planned bidirectional Glenn anastomosis. A decision was made to perform surgery through a left thoracotomy without a cardiopulmonary bypass in order to restore the continuity of the left pulmonary artery.